Triclosan at environmentally relevant concentrations promotes horizontal transfer of multidrug resistance genes within and across bacterial genera. (December 2018) - Lu, Ji; Wang, Yue; Li, Jie; Mao, Likai; Nguyen, Son Hoang; Duarte, Tania; Coin, Lachlan; Bond, Philip; Yuan, Zhiguo; Guo, Jianhua
Abstract: Background: Antibiotic resistance poses an increasing threat to public health. Horizontal gene transfer (HGT) promoted by antibiotics is recognized as a significant pathway to disseminate antibiotic resistance genes (ARGs). However, it is unclear whether non-antibiotic, anti-microbial (NAAM) chemicals can directly promote HGT of ARGs in the environment. Objectives: We aimed to investigate whether triclosan (TCS), a widely-used NAAM chemical in personal care products, is able to stimulate the conjugative transfer of antibiotic multi-resistance genes carried by plasmid within and across bacterial genera. Methods: We established two model mating systems, to investigate intra-genera transfer and inter-genera transfer. Escherichia coli K-12 LE392 carrying IncP- α plasmid RP4 was used as the donor, and E. coli K-12 MG1655 or Pseudomonas putida KT2440 were the intra- and inter-genera recipients, respectively. The mechanisms of the HGT promoted by TCS were unveiled by detecting oxidative stress and cell membrane permeability, in combination with Nanopore sequencing, genome-wide RNA sequencing and proteomic analyses. Results: Exposure of the bacteria to environmentally relevant concentrations of TCS (from 0.02  μ g/L to 20  μ g/L) significantly stimulated the conjugative transfer of plasmid-encoded multi-resistance genes within and across genera. The TCS exposure promoted ROS generation and damaged bacterial membrane, and caused increased expression of the SOS response regulatory genes umuC, dinB and dinD in the donor. In addition, higher expression levels of ATP synthesis encoding genes in E. coli and P. putida were found with increased TCS dosage. Conclusions: TCS could enhance the conjugative ARGs transfer between bacteria by triggering ROS overproduction at environmentally relevant concentrations. These findings improve our awareness of the hidden risks of NAAM chemicals on the spread of antibiotic resistance. Graphical abstract: Highlights: Triclosan promotes ARGs transfer at environmental concentrations. Triclosan provokes bacteria oxidative stress and damage membrane. Bacteria SOS response and ATP synthesis were elevated under triclosan exposure. The applications of triclosan should be cautious and vigilant.